Desenvolvimento e implementação de um aplicativo e um dashboard interativo para o gerenciamento de rotina de um setor de utilidades - Ferreira, Caetano, Nicole (2024)
The digital transformation process and the evolution of Industry 4.0 have promoted digitization as one of the main pillars in various industrial sectors. However, it is crucial to contextualize the importance of this theme, especially in the context of the utilities sector of a glass industry. In this sense, the present research aims to analyze the digital transformation process in this specific sector, with the purpose of identifying possible bottlenecks and areas for improvement, aiming at automating processes for successful implementation. The research objective is to develop and implement an application and an interactive dashboard in the utilities control process of a glass industry company located in Pernambuco. The study is justified by driving digital transformation in this specific sector, identifying opportunities for automation and enhancement, and offering practical solutions to improve operational efficiency and process quality. Methodologically, the research adopts an exploratory approach, combining secondary data and information obtained directly from primary sources, such as managers and operators in the utilities sector, through interviews and observations in the work environment. The main results achieved with the research include the creation of an interactive application. These tools provided a series of significant benefits, such as a reduction of 30 minutes per day in operational work, eliminating the need to transfer data from paper to Excel, and an additional reduction of 10 minutes per day, eliminating manual identification of process deviations. Furthermore, real-time monitoring of operational performance allowed immediate and continuous insight, while enhancing trend visibility. Other benefits included the development of enhanced analytical capacity in management and operations, eliminating the time required for manual data consolidation, and agility in action and assertiveness of countermeasures, enabling a quick and effective response to anomalies or intervention needs